Familial Mediterranean Fever: Current Approaches to Diagnosis and Treatment - Mikhail M. Kostik; Olga V. Zhogova; Natalia V. Lagunova; Sergey V. Ivanovskiy; Oksana L. Kolobova; Larisa N. Melnikova ("Paediatrician" Publishers LLC, 2018)
Familial Mediterranean fever is a typical monogenic disease with an autosomal recessive inheritance pattern; caused by mutations in the MEFV gene, which encodes the pyrin protein. It is a relatively rare pathology in the practice of paediatricians and rheumatologists of the Russian Federation. The article provides up-to-date data on the disease prevalence, presents a complete clinical picture of the auto-inflammatory  syndrome, discusses diagnostic criteria and methods for treating patients with familial Mediterranean fever.